Effects of buprenorphine buccal film and oral oxycodone on pupil diameter in a respiratory study - Webster, MD, Lynn; Cater, PhD, Jacqueline; Smith, MD, Thomas (Journal of Opioid Management, 2022)
Objective: Evaluate the pupillary-constricting effects following administration of buprenorphine buccal film (BBF) and immediate-release (IR) oxycodone. Design: A double-blind, double-dummy, six-treatment, six-period, placebo-controlled, randomized crossover study. Setting: Single-center, phase 1 exploratory pharmacodynamics. Participants: Healthy individuals who self-identify as recreational opioid users, confirmed via a naloxone challenge test on day 1. Interventions: Placebo: BBF 300, 600, and 900 mcg and IR oxycodone 30 and 60 mg. Main outcome measure: Minute ventilation (measured by the ventilator response to hypercapnia) and pupil diameter (determined via standard pupillometry) were assessed predose and at 0.5, 1, 1.5, 2, 2.5, 3, and 4 hours post-dose. Results: Change from baseline in minute ventilation was moderately correlated with change from baseline in pupil diameter during treatment with BBF (Pearson’s r = 0.38-0.40; p ≤ 0.0011) or oxycodone (Pearson’s r = 0.34-0.37; p ≤ 0.005). The initial onset of significant (p < 0.05) pupil constriction relative to placebo occurred at 2, 1.5, and 1 hour after dosing with BBF 300, 600, and 900 mcg, respectively, and at 0.5 hours after dosing with oxycodone 30 or 60 mg. Conclusions: Although BBF and IR oxycodone achieved similar levels of pupil constriction, there was a delayed miosis seen with BBF relative to that found with oxycodone.